Character and Medium: Jack London’s Narrative and The Grey (a Film by John Carnahan) - Montenegro Bonilla, Joe (Escuela de Lenguas Modernas, Universidad de Costa Rica, 2017)
Both literature and cinema tell stories. Nevertheless, stories are told differently on the page than on the screen. This article intends to explain and put into practice an approach to the comparative analysis of literary and cinematic narrative texts; such approach will focus on character and characterization. The category of character will serve as a guiding no- tion for the analysis through an exploration of the various ways in which one lm and three short stories shape their major characters. The lm is The Grey (2011), written and directed by John Carnahan, and the sto- ries are “In a Far Country,” “To Build a Fire,” and “The Law of Life,” all authored by Jack London and evoked by the lm. The intention here is not to establish or explain the extent to which the lm may or may not be considered an adaptation of London’s stories. This is rather an attempt to compare the particular ways in which both media narrate, based on an observation of the different matters of expression that the cinematic and the literary texts use to give life to the characters and their attitudes and realities. Tanto la literatura como el cine cuentan historias. No obstante, estas his- torias se cuentan de manera diferente en la pantalla o en el papel. Este artículo pretende explicar y poner en práctica una estrategia de análisis comparativo de textos narrativos literarios y cinemáticos, la cual se enfoca en los perso- najes y su caracterización. La categoría del personaje servirá como guía para el análisis, a través de una exploración de varias maneras en las que una película y tres cuentos dan forma a sus personajes principales. La película es The Grey (2011), escrita y dirigida por John Carnahan, y las historias, “In a Far Country”, “To Build a Fire” y “The Law of Life”, todas de la autoría de Jack London y evocadas por el lm. La intención no es establecer o explicar hasta qué punto la película puede o no puede considerarse una adaptación de los cuentos de London. Más bien, se trata de comparar las maneras particulares en las que ambos medios narran, con base en una observación de las diferentes materias de expresión que los textos fílmicos y literarios utilizan para dar vida a los personajes y a sus actitudes y realidades.